Transthoracic needle lung biopsy in diagnosis of neoplasms of peripheral localisation - Świerkocki, Krzysztof; Nowicka, Małgorzata; Cofta, Szczepan; Piorunek, Tomasz; Młynarczyk, Witold (Contemporary Oncology/Współczesna Onkologia, 2002)
Transthoracic lung biopsy (TTLB) is an invasive method used in diagnosis of neoplastic lung changes of peripheral localisation. The use of cutting needle enables to obtain relative big samples for histopatology assessment. TTLB is especially helpful, when tissue assessment is required for differential diagnosis of neoplastic lung changes. The reported sensitivity of TTLB depends on the size of the lesion and is usually higher than 70%. Pneumothorax is the most frequent complication but usually only requires drainage in a minority. The risk of pneumothorax appears to be influenced by variables related to the patient, the lesion localisation and its diameter, the technique performance and the experience of the physician. The aim of this study was to assess the usefulness of fluoroscopy guided transthoracic lung biopsy in the diagnosis of possible lung malignances. Between April 2000 and September 2001 in Department of Pulmonary Diseases University of Medical Sciences in Poznań lung biopsies were done in 20 patients (15 male and 5 female) and their age varied from 36-82 years. Transthoracic lung biopsy were done with the use of cutting needle Monojet (Sherwood), 2,1 mm x 150 mm. There were different imaging techniques used in assessment of lung change character and localisation. All the patients had conventional chest radiographs (both posteroanterior and lateral films) performed, some tomograms or computed tomography of the chest. The procedures were performed in radiology laboratory after the patient was local anesthetic. The position of needle was controlled with the use of fluoroscopy. After the procedure lungs were checked for pneumothorax excluded with the use fluoroscopy and chest radiograph in postroanterior projection 4-5 hours later. Tissue specimens were assessed by a pathologist. In 14 patients (70%) lung cancer was diagnosed, in one patient sclerodermia and also in one patient myeloma multiplex and pulmonary absces (together 15%). In 3 patients (15%) no pathological changes were confirmed. Occurence of abnormalities in lungs were similar (11 in right lung and 9 in left lung), but more changes appeared in left lower lobe and right upper lobe (adequate 8 and 6). In assessed group no pathological changes in middle lobe were found . Four patients developed pneumothorax but they did not require drainage. Transthoracic lung biopsy is an effective method in diagnosis of pulmonary malignancies. In many cases it dimishes the need for more invasive surgical diagnostic methods.